Protecting the Polar Marine Environment - Law and Policy for Pollution Prevention - VIGNI, PATRIZIA (2002)
This book review highlights the importance of the strict cooperation between lawyers and scientists with regard to the protection of the polar environment. The issues that have been raised in this book review have currently become the most important matter at stake both within the group of Arctic States and the Antarctic Treaty system